TEACHING ENGLISH TENSES TO BEGINNERS: A COMPARATIVE ANALYSIS OF TRADITIONAL AND TECHNOLOGY-ENHANCED METHODS (European Journal of Interdisciplinary Research and Development, 2025)
Teaching English tenses to beginners is a core component of early language instruction, yet educators continue to debate whether explicit grammar-focused instruction or technology-enhanced contextual teaching is more effective. This study compares the effectiveness of two methods — traditional grammar rule explanation and technology-enhanced contextual teaching — in improving beginner learners’ mastery of the Present Perfect Simple tense. A total of 24 beginner-level learners were randomly assigned to two groups. Group A was taught using traditional grammar-focused instruction, while Group B received instruction via multimedia resources and contextual examples. Both groups completed a pre-test and post-test assessing grammar accuracy and communicative fluency. As a result both methods led to measurable improvements in accuracy and fluency. Group A demonstrated higher gains in grammar accuracy (16% increase), while Group B achieved greater improvement in communicative fluency (13%% increase). Findings suggest that while traditional instruction is more effective for explicit grammar accuracy, technology-enhanced contextual teaching is more effective for promoting fluency. A blended approach that incorporates both methods may offer the most balanced learning outcomes for beginner English learners.